FACTORS CAUSING LANGUAGE LOSS EXPERIENCED BY AN AMERICAN NATIVE SPEAKER IN MULTILINGUAL SITUATION IN INDONESIA - Saptina Retnawati (ELT-Lectura, 2018)
Bilingualism and multilingualism are common phenomena in language use. Those who are bilinguals or multilingual normally get the language competence because they are living in multilingual area, or in a country which has variety of languages and cultures. Indonesia is one of countries which have this wide diversity in cultures, languages, and religions. Furthermore, Indonesian Ministry of Education created a program called Darmasiswa program which enabled students from abroad to study Bahasa Indonesia and Indonesian cultures. By following this program, those students are learning new language and culture in multilingual situation. One of evidences occurred with a student from America, named Angela who also has multilingual family background. She was exposed to a lot of languages since she was born, and she also studied new languages in Indonesia, as a result she has capability to speak more than two languages. In this kind of situation, the researcher was interested to find out the language loss she might experience during her study. This study aimed to find factors influenced on language loss by her. The approach of this study was qualitative. The researcher applied mixed techniques to obtain data; recording the conversations in natural setting and interview. The analysis was interpretive. The findings of this study found that there were two factors that influenced language loss; internal factors and external factors, which dominated by cultural factor. Also, it happened because of the fact that Bahasa Indonesia is more dominant than her mother tongues.